2022
DOI: 10.2174/18742106-v16-e2110281
|View full text |Cite
|
Sign up to set email alerts
|

3D Facial Analysis in Class II Subdivision Malocclusion

Abstract: Background: Class II subdivision is an asymmetric condition presenting a Class I dental occlusion on one side and a Class II on the contralateral one. It presents a midline deviation that may be caused by a monolateral distalization of the mandible (type 1) or a mesialization of one side of the maxilla (type 2). The evaluation of asymmetry based on 2D radiographic records has been demonstrated to be less accurate than the one made using 3D radiographs. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…3D Facial profile is considered dependent on dentoskeletal tissue and overlying soft tissue. Studies indicated the strong correlation between the 3D soft tissue facial profile and the skeletal pattern [ 6 , 7 ]. For example, for a typical class II hyperdivergent patient, sagittal and vertical inharmonious statuses cause retrusive and clockwise rotated mandible that leads to convex facial profile with excessive lower facial height.…”
Section: Introductionmentioning
confidence: 99%
“…3D Facial profile is considered dependent on dentoskeletal tissue and overlying soft tissue. Studies indicated the strong correlation between the 3D soft tissue facial profile and the skeletal pattern [ 6 , 7 ]. For example, for a typical class II hyperdivergent patient, sagittal and vertical inharmonious statuses cause retrusive and clockwise rotated mandible that leads to convex facial profile with excessive lower facial height.…”
Section: Introductionmentioning
confidence: 99%